ANALISIS KELAYAKAN USAHA PETERNAKAN AYAM PETELUR (STUDI KASUS DI CV ILWA FARM KABUPATEN BLITAR) - Dendo, Bernardus Bili; Supartini, Nonok; Santoso, Erik Priyo (Fakultas Pertanian, 2019)
Efforts to obtain large and sustainable profits are the main target for all business activities, including laying chicken farms, which in turn will improve the welfare of the laying hens. The purpose of this study is to analyze the benefits of B / C (ROI), ROI (Return On Investment) and BEP (Break Event Points) by the Ilwa Farm of Blitar Regency. The type of research used is a case study. This research will be carried out on laying hens companies namely CV. Ilwa Farm in Blitar district. The technique of collecting data uses the method of observation and documentation. The collected data is tabulated and analyzed using a descriptive and mathematical analysis model approach. The mathematical analysis model approach is intended to analyze the allocation of production costs and the level of profit (profit) in laying hens company CV. Ilwa Farm through the profit analysis model, Return of Investment (ROI), B / C Ratio and BEP (Break Even Point). The profit of Ilwa Blitar farm is Rp. 7,201,293,947 per period. The average income of Ilwa Farm for one month is Rp. 342,918,759. The results of the calculation of B / C Ratio obtained a value of 3.1, which means that the value of the B / C Ratio Ilwa Blitar farm is> 1 means that the business is worth trying. The ROI value is 2.1% while the prevailing interest rate is 1.15% per year. So it can be concluded that Ilwa Farm chicken farm is worth the effort. The value for BEP Ilwa Farm farms broke even when egg production was 195,004 kg. And the price of eggs at Ilwa Farm is break even at Rp. 5,637. Upaya memperoleh keuntungan dan berkelanjutan merupakan sasaran utama bagi semua kegiatan usaha peternakan ayam petelur, yang akhirnya akan meningkatkan kesejahteraan bagi pelaku usaha peternakan ayam petelur tersebut. Tujuan dalam penelitian ini adalah menganalis keuntungan nilai B/C ( Benefit Cost Ratio), ROI (Return On Investment) dan BEP (Break Event Poin) diperusahan ayam petelur Ilwa Farm Kabupaten Blitar. Jenis penelitian yang digunakan adalah studi kasus. Penelitian ini dilaksanakan pada perusahan ayam ras petelur yakni CV. Ilwa Farm di kabupaten Blitar. Teknik pengumpulan data menggunakan metode observasi dan dokumentasi. Data yang dikumpulkan ditabulasi dan dianalisis dengan menggunakan pendekatan model analisis deskriptif dan matematik. Pendekatan model analisis matematik dimaksudkan untuk menganalisis alokasi biaya produksi dan tingkat keuntungan (profit) pada perusahaan ayam ras petelur CV. Ilwa Farm melalui model analisis keuntungan (profit), Return Of Invesment(ROI), B/C Ratio dan BEP (Break Even Point). Laba peternakan Ilwa Blitar adalah Rp. 7.201.293.947 per periode. Pendapatan peternakan Ilwa Farm selama satu bulan adalah Rp.342.918.759. Hasil perhitungan B/C Ratio didapatkan nilai sebesar 3,1 yang berarti nilai hitung B/C Ratio Ilwa farm Blitar adalah > 1 berarti usaha tersebut layak untuk diusahakan. Nilai ROI adalah 2.1% sedangkan tingkat suku bunga yang berlaku adalah 1.15% per tahun. Sehingga dapat disimpulkan bahwa usaha peternakan ayam Ilwa Farm layak diusahakan. Nilai untuk BEP peternakan Ilwa Farm mencapai titik impas pada saat produksi telur ke 195.004 kg. Dan harga telur di peternakan Ilwa Farm mencapai titik impas pada harga Rp. 5.637.